Act now! Covid-19 pandemic: the coordinated support of the international community to low- and middle-income countries is needed immediately - Brugnara Kirchmann, Lúcia; Marx, Michael (International journal for quality in health care, 2021)
Since the first alert of Covid-19 on 31st of December 2019, around 4 million cases have been confirmed worldwide and over 260 000 people died according to the World Health Organization (WHO) [1]. Countries all over the world closed their borders, services were shut down and restrictions are imposed with the aim of ‘flattening the curve’ to relieve the pressure on the health system. In the history of humanity, global public health awareness has probably never been as high as these days.So far, most cases have been registered in countries in Asia, Europe and in the last weeks in North America, but the impact of the pandemic can be already seen in other regions as well: by the first week of April the morgues of Guayaquil, Ecuador’s largest city, were full and corpses of Covid-19 victims were left in the streets [2]. A recently published study projects that the Covid-19 death cases in Brazil and Nigeria could rise as high as 500 000 and 140 000, respectively, whereby authors here consider only countries´ population age structure [3]. The situation might be aggravated by other factors like poor access to health services, insufficient medical supplies or erratic political decisions. The WHO health system building blocks framework [4] provides orientation for a situation analysis.
Advance access publication date: 13 May 2020
Gesehen am 24.06.2021